Talent Management On Individual Work Performance: Managerial Support As A Mediator - Rajendra Zaid Adiyanto; Annisa Fajri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This paper examines the influence of perceived organizational support on employee performance and overall success. An effective talent management process can improve individual work performance by providing appropriate rewards to employees who do their jobs and achieve targets, thereby contributing to individual and organizational success. The research results also show that the mediating influence of work involvement or perceived organizational support has a significant influence on employee creativity and indirectly influences employee creativity. Setting clear and achievable work goals or targets is important for an effective performance appraisal process.